Business & The Sustainable Development Goals A Framework for Effective Corporate Involvement - van Tulder, Rob (RSM Series on Positive Change, 2018)
This short book presents a framework for making corporate strategies effective for sustainable development. This framework is a condensed result of a variety of interdisciplinary research and teaching projects, organised with colleagues in academia, practitioners at companies, civil society organisations and government, and with PhD and master students. Over the course of a considerable number of years these collaborations allowed me to develop a more integrated vision on the way corporations could effectively contribute to very complex societal problems: through new business models, cross-sector partnerships, thinking on inclusive development, linking macro challenges to micro approaches, positive change trajectories and all sorts of management techniques that are needed to (pro) actively take up complex societal challenges (rather than staying passive or shift responsibility to others).